Clinical characteristics, complications and satisfaction of megameatus intact prepuce (MIP) hypospadias variant: a 15 year retrospective study - Meng He; Songqiao Fan; Ning Sun; Jun Tian; Minglei Li; Hongcheng Song; Weiping Zhang (BMC Urology)
Abstract Background To analyze the clinical characteristics, complications and patients satisfaction of MIP hypospadias variant. Methods A retrospective analysis was performed for 31 patients with MIP admitted to our hospital from January 2008 to February 2023. All enrolled patients underwent telephone follow-up and a survey was conducted on the satisfaction of patients and their families. Outcome analysis was focused on clinical data includes age, position of the meatus, penile curvature, type of repair, complications and satisfaction survey results. Statistical analyses were performed using R software. Results The average age of 31 MIP patients was 92.1 ± 40.7 months, and the median follow-up time was 49.0 [21.0–82.2] months. Twenty one patients (67.7%, 21/31) had ventral curvature and no dorsal curvature was observed. All cases were divided into chordee group and no chordee group. There was a statistical difference in age (80.4 ± 41.6 Vs 117.0 ± 26.0 months) and weight (22.7 [15.8–35.0] Vs 45.0 [32.0–46.0] kg) between the two groups. Six children (19.4%, 6/31) experienced post-operative complications; however, none required reoperation. The only risk factors for complications were the meatus position and whether urethroplasty was performed.Only the occurrence of complications may affect patients satisfaction. Conclusions MIP hypospadias variants can exhibit severe ventral curvature. Surgery can achieve good results with a low incidence of complications. A satisfactory skin appearance and adequate curvature correction are key concerns for both patients and parents.